Dinámica espacio-temporal de la producción camaronera en la Isla Puná del cantón Guayaquil, provincia de Guayas. - Ramírez Narváez, Manuel Esteban (2019)
Puná Island in the province of Guayas is an area where shrimp activity has developed since the 80's with extensive crops and until recent years this industry has gained considerable areas leaving as a sequel the loss of large areas of mangrove forest, overlooking the ecological importance of these. The present study was elaborated with the objective of "Determining the spatiotemporal variation of shrimp production through the application of remote sensing techniques for the detection of changes in Isla Puná, Guayaquil canton, province of Guayas between 1985 and 2016", where the change in land use and its subsequent quantification was investigated. The GRASS GIS software was used to carry out this work, where the satellite images were pre-processed to make geometric and atmospheric corrections. Digital enhancements were also made in order to obtain a visual improvement in the satellite images. Afterwards, the Qgis software proceeded to perform the classification supervised by the method of maximum likelihood and maximum sequentiality a posteriori, identifying 7 classes of land use (shrimp, mangroves, clouds, dry scrubland forest, bare soil, bodies of water-erial and salt-playon areas), which were then quantified. Finally, the results were validated with a confusion matrix, obtaining errors of omission, commission, global precision and the Kappa statistic. Based on the above, the results obtained showed that shrimp production showed considerable variations, increasing its surface from 6 819,3 Ha in 1985 to 13 832,01 Ha in 2016, a dynamic that has left as sequels the loss of mangrove forests, as these areas were reduced from 10 931,31 Ha in 1985 to 5 282,82 Ha in 2016. According to the literature researched, these changes are due to events that occurred throughout history, such as the arrival of the shrimp boom in the 80's on Puná Island, the large losses of shrimp farming due to the white spot plague and its subsequent recovery, and above all, the lack of compliance with and rigorous application of current regulations. Keywords: Remote sensing, land use, shrimp production, spatio-temporal variation, mangrove forest.